Numerical study of corrosion in high pressure vent pipelines at high sulfur natural gas stations considering liquid phase accumulation and erosion - Li, Jing; Shen, Jun; Tan, Longhua; Zhang, Liang; Du, Defei; Liao, Yihong; Zhu, Xingyu (Frontiers in Materials, 2025)
In high-sulfur natural gas stations, vent pipelines, especially at their elbows, experience acidic corrosion and erosion, which affects the safety of the pipelines. On-site wall thickness measurements of pipelines are empirical and random, failing to provide a comprehensive and accurate reflection of the corrosion status of the entire vent pipeline. This study used computational fluid dynamics (CFD) to simulate an actual high-pressure vent pipeline. By analyzing the flow field distribution, the location of liquid phase accumulation was determined, and the areas of severe erosion were identified. This information can provide a basis for selecting reasonable corrosion measurement points on-site.